COMPARATIVE STUDIES ON THE EFFICIENCY AND TOLERABILITY OF FOUR ANTIMALARIALS IN MALARIAL PATIENTS OF DIFFERENT HAEMOGLOBIN GENOTYPES (AA, AS, AND SS)
Comparative studies on the efficiency and tolerability of four antimalarial, quinine dihydrochloride, sulfadoxine/pyrimethamine, halofantrine and artesunate were carried out in 480 volunteer malaria patients of different HB - genotypes (AA, AS, and SS). Patients with HB - genotype AA were 350 (73%). Those with HB - genotype AS were 102 (21.2%) and those with HB - genotype SS were 28 (5.8%), those with HB genotype AA were randomly divided into four groups of 34, 88, 90 and 90 patients each. Those with HB genotype AS were randomly divided into four groups of 25, 25, 26, 26 patients each and those with HB genotype SS were divided into four groups of 6, 7, 7 and 8-patients each. First group received sulfadoxine/pyrimethamine, 3 tablets of 500mg/25mg orally at once. Second group received quinine dihydrochloride 200mg or 8mg/kg 3 times daily for 6 days. Third group received halofantrine 160mg tablets (start) and 80mg 6 hourly for 3 days orally. Fourth group received artesunate 100mg tablets (start) and 50mg 12 hourly for 5 days orally. On day 7 efficacy of these antimalarials was evaluated and compared according to different hemoglobin genotypes AA, AS, and SS. Artesunate had the highest efficacy of 98% in AA, 93.3% in AS and 100% in SS. The efficacy of artesunate is not significantly different (P>0.05) in AA, AS and SS. Halofantrine ranked second in efficacy with 97.8% in AA, 92.06 % in AS and 85.7% in SS. Efficacy of halofantrine is not significantly different in these HB - genotypes (P>0.05